Edukasi Air Kelapa Muda Bagi Kesehatan: Education on the Benefits of Young Coconut Water for Health - Sintiya Halisya Pebriani; Lily Marleni; Adi Saputra; Mardiah Mardiah; Tafdhila Tafdhila; Lenny Astuti; Rahmalia Afriyani; Abdul Syafe'i (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Tender coconut water is an isotonic drink that contains various kinds of minerals, vitamins, and sugars as well as essential amino acids that are very beneficial for the body. The purpose of this service activity is to provide health education about the efficacy of tender coconut water to maintain health. The method used is lecture, question and answer and discussion. The media for counseling is leaflets. The results of the activity went smoothly and were attended by 19 participants and the majority of participants understood the various benefits of tender coconut water for health. It was concluded that most of the participants knew the various benefits of tender coconut water in order to maintain and improve optimal health. ABSTRAK Air kelapa muda merupakan minuman isotonik yang mengandung berbagai macam mineral, vitamin, dan gula serta asam amino sesensial yang sangat bermanfaat bagi tubuh. Tujuan dari kegiatan pengabdian ini adalah untuk memberikan pendidikan kesehatan mengenai khasiat air kelapa muda untuk menjaga kesehatan. Metode yang digunakan yaitu dengan ceramah, tanya jawab dan diskusi. Media penyuluhan yaitu dengan leaflet. Hasil kegiatan berjalan dengan lancar dan dihadiri sebanyak 19 perserta dan mayoritas peserta memahami berbagai manfaat air kelapa muda bagi kesehatan. Disimpulkan Sebagian besar perserta mengetahui berbagai manfaat air kelapa muda guna menjaga dan meningkatkan kesehatan secara optimal.